The Role of Using Cell Phones and the Internet on Miscarriage: a Case-control Study - Masoumeh Mosayebi-Molasaraie; Shamim Pilehvari; Amin Doosti-Irani; Zahra Cheraghi (Journal of Midwifery & Reproductive Health, 2023)
Background & aim: Despite the concerns about using cell phones and internet on women's reproductive health, few studies have considered this issue, with most focusing on animal models. The present study was conducted to examine the effect of using cell phones and internet on miscarriage.Methods: In this case-control study, a sample of 211 cases and 394 controls were selected through stratified random sampling from women referred to urban health centers in Zanjan in 2019. Data on telephone and internet use was collected using a self-administered questionnaire, while health records were collected using a checklist. Women with miscarriage history were chosen randomly as the case and women with a successful pregnancy history as the control.Results:   Considering the average internet use per hour, and with the effect of other variables remaining constant, the odds of miscarriage increased, and this association was borderline significant (OR=1.07, 95% CI: 0.99, 1.15, P=0.050). Meanwhile, for every hour of cell phone conversations during pregnancy, although the odds of miscarriage increased, but this association was not statistically significant (OR=1.12, 95% CI: 0.86, 1.45, P=0.380). Similarly, turning off cell phones at night decreased the odds of miscarriage, but this association was also not statistically significant (OR=0.97, 95% CI: 0.58, 1.61, P=0.380).Conclusion: Although the effect of internet use on miscarriage was small and had borderline statistical significance, it appears reasonable to take preventive measures to reduce exposure to low-frequency electromagnetic waves by pregnant women.